CD163 and CD206 expression define distinct macrophage subsets involved in active ANCA-associated glomerulonephritis. Issue 133 (December 2022) - Aendekerk, Joop P.; Jiemy, William F.; Raveling-Eelsing, Elisabeth; Bijnens, Nele; Abdul-Hamid, Myrurgia A.; Strating, Inge M.; Dekkema, Gerjan J.; Sanders, Jan-Stephan F.; Stegeman, Coen A.; Damoiseaux, Jan G.M.C.; Little, Mark A.; Heeringa, Peter; et al.
Abstract: Introduction: Macrophages are key players in the immunopathology of anti-neutrophil cytoplasmic antibody (ANCA) mediated-vasculitis (AAV) with glomerulonephritis (ANCA GN). Different macrophage phenotypes are expected to play distinct roles in ANCA GN. Macrophages expressing CD163 and CD206 are found in lesions associated with ANCA GN. Hence, we aimed to investigate the clinicopathological significance of CD206 and CD163 in ANCA GN in a multicenter retrospective cohort study. Material and methods: Patients with ANCA-associated vasculitis, with clinical data, serum and urine samples were included from three cohorts. Serum soluble CD206 (ssCD206) and urinary soluble CD163 (usCD163) levels were measured. Human kidney tissue samples ( n  = 53) were stained for CD206 and CD163 using immunohistochemistry and immunofluorescence, and findings were correlated with clinical and pathological data. Results: In total, 210 patients were included (i.e., ANCA GN, n  = 134; AAV without GN, n  = 24; AAV in remission n  = 52). Increased levels of both ssCD206 and usCD163 were seen in ANCA GN. High levels of ssCD206 declined after reaching remission, however, ssCD206 did not improve the accuracy of usCD163 to detect ANCA GN. Soluble markers correlated with histopathological findings. CD163 + CD206 - macrophages were found in the glomerulus and may play pivotal roles in glomerulonephritis, whereas CD206 + CD163 - and CD206 + CD163 + macrophages were located tubulointerstitially and likely play a more prominent role in ANCA-associated tubulointerstitial inflammation. In ANCA GN patients increasing levels of ssCD206 increased the risk for end-stage renal disease and mortality. Conclusions: Our results confirm and extend the notion that CD206 + and CD163 + macrophages are prominent components of the cellular infiltrate in ANCA GN. We found distinct macrophage phenotypes that may play distinct roles in the immunopathology of ANCA GN and elaborate on a potential mechanism underlying the findings of this study. usCD163 remains an excellent marker to detect active ANCA GN, whereas ssCD206 seems a more prominent marker for risk prediction. Highlights: Distinct macrophage subsets can be found in biopsies of ANCA GN patients. Distinct macrophage subsets correlate with histopathology and soluble markers. Macrophage subsets can help assess treatment response & risk stratification in ANCA. UsCD163 reflects ANCA GN activity. SsCD206 can be useful for treatment response, prognosis for ESKD and death in ANCA.